1994
DOI: 10.1172/jci117521
|View full text |Cite
|
Sign up to set email alerts
|

Block of AIDS-Kaposi's sarcoma (KS) cell growth, angiogenesis, and lesion formation in nude mice by antisense oligonucleotide targeting basic fibroblast growth factor. A novel strategy for the therapy of KS.

Abstract: Kaposi's sarcoma (KS) is the most frequent tumor of HIV-1-infected individuals (AIDS-KS). Typical features of KS are proliferating spindle-shaped cells, considered to be the tumor cells of KS, and endothelial cells forming blood vessels. Basic fibroblast growth factor (bFGF), a potent angiogenic factor, is highly expressed by KS spindle cells in vivo and after injection in nude mice it induces vascular lesions closely resembling early KS in humans. Similar lesions are induced by inoculating nude mice with cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 31 publications
(78 reference statements)
0
54
0
Order By: Relevance
“…In the previous reports, tumor suppression by inhibition of FGFs has been achieved using: ( a) a neutralizing antibody against FGF -2, 22,23 ( b ) antisense oligonucleotides against FGF -2, 24 (c ) antisense RNA for FGF -2, 25 (d ) antisense FGF -2 DNA, 26 and ( e) anti -FGF chemicals such as carboxymethyl benzylamide dextran. 27 Our results are consistent with those findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous reports, tumor suppression by inhibition of FGFs has been achieved using: ( a) a neutralizing antibody against FGF -2, 22,23 ( b ) antisense oligonucleotides against FGF -2, 24 (c ) antisense RNA for FGF -2, 25 (d ) antisense FGF -2 DNA, 26 and ( e) anti -FGF chemicals such as carboxymethyl benzylamide dextran. 27 Our results are consistent with those findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this system KSC induce formation of angioproliferative lesions of mouse cell origin closely resembling human early KS (2)(3)(4). By using this model, we found that paclitaxel promotes regression of KS lesions in vivo.…”
mentioning
confidence: 86%
“…Primary spindle cell cultures derived from AIDS-KS lesions (KS6, KS8, and KS12 strains; passages 8 -12) were derived and cultured as already described (2,4,6,56,57). Lesional spindle cells are latently infected by HHV-8 in vivo but lose the virus upon culture in vitro (58).…”
Section: Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neutralizing anti-basic FGF antibodies or antisense oligodeoxynucleotides do not totally block lesion formation after inoculation of KS cells in mice [155] and injection of basic FGF alone does not induce the edema characteristic of KS [74]. This suggests involvement of other factors.…”
Section: The Role Of Angiogenic Inducers In Kaposi's Sarcomamentioning
confidence: 96%